The Effectiveness of Utilizing Wordwall Educational Game Media in Al Quran Hadith Lessons to Enhance Student Motivation and Learning Outcomes - Tika Nurul Hidayati; Mawardi Lubis; Husnul Bahri (FKIP - Universitas Riau, 2026)
This study aims to evaluate the effectiveness of using Wordwall educational game media in improving motivation and learning outcomes for grade VII students in the Al-Qur'an Hadith subject at MTsN 1 Bengkulu City. Employing an evaluation research design with a comparative approach, the study utilized a simple combination method. Data were gathered through observation, learning motivation questionnaires, learning outcome tests, and documentation. Data analysis compared motivation and learning outcomes before and after the use of Wordwall media. The findings indicated a significant increase in both student motivation and learning outcomes. The planning stage achieved an effectiveness level of 86.36%, showing that the integration of Wordwall educational game media into lesson planning was well-executed. During the implementation phase, the effectiveness reached 91.09%, with pre-motivation scores at 83.79% and post-motivation at 88.97%, reflecting a 5.18% improvement. Pretest learning outcomes were at 57.79% (classified as